Work Environment Factors And Job Performance: The Construction Project Manager’s Perspective - Abdul Razak, Arman; Jaafar, Mastura; Abdullah, Shardy; Muhammad, Samsiah (2009)
Project performance is a critical issue for the construction industry. Project deliverables such as timely completion and client satisfaction are often used as yardsticks to determine success. More often that not, the success of a construction project hinges on the ability of the construction project manager to effectively perform his job functions with the intended efficacy. As such this paper intends to firstly identify the relationship between work environment factors and job performance and secondly to rank these work environment factors in the order of importance. Respondents comprising of project managers in construction firms throughout the northern region of Peninsular Malaysia were selected as the sample population. Questionnaires were then distributed and collected. From the analysis conducted on the gathered data, it was found that the performance level of the project manager had a very high correlation with the level of authority as well as the type of client within a specific project.